786 Distinct efficacy and immunological responses to aPD-1, aPD-L1 and aPD-L2 immunotherapy in B16 melanoma in aged versus young hosts includes T-cell stem cell effects and PD-L2 expression differences. (9th November 2020) - Garcia, Myrna; Padron, Alvaro; Deng, Yilun; Kancharla, Aravind; Reyes, Ryan; Gupta, Harshita; Curiel, Tyler
Abstract : Background: Aging is the biggest risk factor for cancer, yet little is known about cancer immunotherapy effects. ?PD-1 can block PD-L1 and PD-L2 while ?PD-L1 blocks PD-1 and CD80. 1 A recent key finding in young hosts including humans is that melanoma response to aPD-1/aPD-L1 correlates with CD8+TCF-1+ T cell stem cell (TCSC) generation. 2 Methods: We tested aPD-1 (100 or 200 µg/mouse), aPD-L1 (100 µg/mouse) or aPD-L2 (200 µg/mouse) in aged (18-33 months) and young (3-8 months) mice challenged orthotopically with B16 (WT or PD-L1ko) melanoma (SQ) or ID8agg ovarian cancer (IP). Tumors were analyzed by flow. Bone marrow-derived DC were generated with GM-CSF. Results: We reported that aPD-1 treats young and aged with B16 and aPD-L1 treats young not aged. 3 aPD-L2 treated B16 in aged but, remarkably, not young, the first anti-cancer single agent immunotherapy exhibiting this property [figure 1]. Efficacy in young (aPD-1, aPD-L1) and aged (aPD-L2) correlated with increased tumor TCSC [figure 3], but TCSC differed by age and treatment (e.g., distinct CCR2, CXCR5, CXCR3) [figure 2]. aPD-L2 efficacy against B16 in aged mice required host IFN-g and IL-17 [figure 4]. IP ID8agg ovarian cancer did not respond to aPD-L2 in aged or young mice. Aged expressed up to 40-fold more PD-L2 versus young on various immune cells suggesting high PD-L2 helps aPD-L2 response [figure 6]. Host IFN-g contributed to aged PD-L2 expression, which did not appear cell-autonomous [figure 6]. PD-L1KO aged but not young mice challenged with PD-L1KO B16 responded to aPD-1 [figure 5], consistent with PD-L2 block as a mechanism. Conclusions: Treatment differences in aged versus young could depend on immune checkpoint or TCSC differences, which could be related to CD8+ T-cell infiltration, including TCSC. aPD-1 efficacy in aged PD-L1KO mice challenged with PD-L1KO B16 suggests that aPD-1 efficacy is through PD-L2 block in aged. PD-L2 expression differences and anatomical compartment differences in tumor microenvironment may also contribute to treatment efficacy differences. We are now identifying mechanisms for increased PD-L2 and other mechanisms for aPD-L2 efficacy in aged, and testing TCSC effects. Our work can improve cancer immunotherapy in aged hosts and provides insights in treatment failures, including in young hosts. Acknowledgements: South Texas MSTP training grant (NIH T32GM113896), TL1TR002647, Graduate Research in Immunology Program training grant (NIH T32 AI138944), R01 CA231325, Samuel Waxman Cancer Research Foundation Grant Ethics Approval: The study was approved by UTHSA IACUC, approval number 20180021. References: Schildberg FA, Klein SR, Freeman GJ, Sharpe AH. Coinhibitory pathways in the B7-CD28 ligand-receptor family. Immunity 2016;44(5):955-72. Im SJ, Hashimoto M, Gerner MY, Lee J, Kissick HT, Burger MC, et al. Defining CD8+ T cells that provide the proliferative burst after PD-1 therapy. Nature 2016;537(7620):417-21. Padron A, Hurez V, Gupta HB, Clark CA, Pandeswara SL, Yuan B, et al. Age effects of distinct immune checkpoint blockade treatments in a mouse melanoma model. Exp Gerontol 2018;105:146-54.